Well – being Parameter Evaluation for Athlete Homestead in Jakarta - Stephen Yona Loanoto; Maria Imaculata Hidayatun; Rully Damayanti (Advances in Civil Engineering and Sustainable Architecture, 2019)
This research discusses Koen Steemer’s theory of human well-being forathlete village. The sustainability of an athlete village, post-event, proves to be amodern controversy. Architecture often omits the sustainability factor of the athletevillage. As a result, the main question would be “how to design an effective wellbeingathlete village?” where Steemer’s parameters or an enhanced version of it,could be incorporated into Indonesia’s own athlete village. This discussion willutilize the first person phenomenology method. Koen Steemer’s “Seven DesignStrategy” parameter is used to analyze four precedent Olympic Village studiesbetween the years 2004 to 2016. In addition, an interview with an Indonesian“athlete village” specialist was conducted. As a result, an enhanced parameter ofSteemers’s theories is established.